Answer:
Option D is correct.
The equation with roots 3 plus or minus square root 2 is x² - 6x + 7
Step-by-step explanation:
The roots of the unknown equation are
3 ± √2, that is, (3 + √2) and (3 - √2)
The equation can then be reconstructed by writing these roots as the solutions of the quadratic equation
x = (3 + √2) or x = (3 - √2)
The equation is this
[x - (3 + √2)] × [x - (3 - √2)]
(x - 3 - √2) × (x - 3 + √2)
x(x - 3 + √2) - 3(x - 3 + √2) - √2(x - 3 + √2)
= x² - 3x + x√2 - 3x + 9 - 3√2 - x√2 + 3√2 - 2
Collecting like terms
= x² - 3x - 3x + x√2 - x√2 - 3√2 + 3√2 + 9 - 2
= x² - 6x + 7
Hope this Helps!!!
Answer:
x = 7
Step-by-step explanation:
Given
4x + 13x = 119 ( collect like terms on left side )
17x = 119 ( divide both sides by 17 )
x = 7
108<9•12
^. ^
3•3 2•6
^. ^
1•2 3•2
Answer:
hahahahahahaahahaha i dont know the answer i dont care to
Step-by-step explanation: